2013
DOI: 10.15835/nbha4118307
|View full text |Cite
|
Sign up to set email alerts
|

The Mineral Source for Human Nutrition of Nuts in Different Hazelnut (Corylus avellana L.) Cultivars

Abstract: Hazelnuts (Corylus avellana L.) have a significant place among the types of dried nuts in terms of nutrition and health owing to their special composition of fats, protein, carbohydrates, vitamins, minerals, dietary fibers and phenolic antioxidants. Different hazelnut cultivars grown in Romania ('Cozia' , 'Romavel' , 'Valcea 22' , 'Roverd' and 'Red Lambert') were evaluated for their mineral composition. Microelements were determined by using ICP-MS and a Flame AAS. The average microelements concentrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
5
20
3
Order By: Relevance
“…The tested nuts were also rich in micronutrients, with highest amounts of Ca, Fe, Mg, P and Zn in almonds, whereas hazelnuts were rich in Cu and Mn (Table 2). These results are in concordance with others (Alasalvar & Shahidi, 2009;Cosmulescu, Botu, & Trandafir, 2013) with slight differences. Cosmulescu et al (2013) analysed the mineral composition of hazelnuts from different cultivars and showed that the mineral composition depends on cultivar conditions, which could explain variations in the mineral content of nuts and also in the content of macronutrients compared to our results.…”
Section: Resultssupporting
confidence: 94%
“…The tested nuts were also rich in micronutrients, with highest amounts of Ca, Fe, Mg, P and Zn in almonds, whereas hazelnuts were rich in Cu and Mn (Table 2). These results are in concordance with others (Alasalvar & Shahidi, 2009;Cosmulescu, Botu, & Trandafir, 2013) with slight differences. Cosmulescu et al (2013) analysed the mineral composition of hazelnuts from different cultivars and showed that the mineral composition depends on cultivar conditions, which could explain variations in the mineral content of nuts and also in the content of macronutrients compared to our results.…”
Section: Resultssupporting
confidence: 94%
“…Among the studied elements, potassium was the most abundant mineral in hazelnut. Potassium contents in this study were higher than those reported by Açkurt et al , Özdemir and Akıncı and Güneş et al for ‘Tombul’ variety (5267.2, 5516 and 5602.0 mg kg −1 respectively), similar to that of Cosmulescu et al for Romanian varieties (6173.4 mg kg −1 ) and lower than that of Köksal et al for ‘Tombul’ variety (8140 mg kg −1 ). Potassium is important for a healthy nervous system and a normal heart rate .…”
Section: Resultssupporting
confidence: 58%
“…Zinc fertilizers did not have a significant effect on the phosphorus content of kernels, which ranged from 3002.7 mg kg −1 at 0.2 kg Zn ha −1 to 3197.3 mg kg −1 at 1.6 kg Zn ha −1 (Table ). These phosphorus contents were higher than that found by Köksal et al (2880 mg kg −1 ) but lower than those reported by Özdemir and Akıncı (3298 mg kg −1 ) and Cosmulescu et al (3006.7–4550.6 mg kg −1 , Romanian cultivars) The mean phosphorus content in kernels was 3131.8 mg kg −1 with zinc fertilizations (Table ). Phosphorus is a component of bones and cells and is involved in energy processing and many other functions.…”
Section: Resultscontrasting
confidence: 48%
See 2 more Smart Citations